2007
DOI: 10.1521/aeap.2007.19.6.511
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Positive AIDS Care Messages Among Service Providers in China

et al.

Abstract: There is great potential in adapting the popular opinion leader (POL) intervention model to address HIV-related stigma and quality of care among service providers in China. Using a representative sample of 1,101 service providers in China, this study provides preliminary descriptions of POL provider characteristics. Multiple regression analyses revealed that diffusion of positive AIDS care messages among service providers in China was associated with factors such as gender, ethnicity, medical education, level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The POL providers in this study reported significantly higher levels of message diffusion than non-POLs at baseline, suggesting that the strategies used in POL selection were effective in terms of identifying those who were more capable of communications and more willing to share their thoughts with their coworkers. We also found that female providers reported a higher level of message diffusion, and they were more likely to be selected as a POL; this result was consistent with our previous findings (Li et al, 2007a). Previous researchers have reported that women in general are much more involved and active in communication and social activities than men (Behrman, Kohler, & Watkins, 2002; Shklovski, Kraut, & Rainie, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The POL providers in this study reported significantly higher levels of message diffusion than non-POLs at baseline, suggesting that the strategies used in POL selection were effective in terms of identifying those who were more capable of communications and more willing to share their thoughts with their coworkers. We also found that female providers reported a higher level of message diffusion, and they were more likely to be selected as a POL; this result was consistent with our previous findings (Li et al, 2007a). Previous researchers have reported that women in general are much more involved and active in communication and social activities than men (Behrman, Kohler, & Watkins, 2002; Shklovski, Kraut, & Rainie, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…A scale to measure Diffusion of HIV Care Messages was developed and validated in a previous investigation (Li et al, 2007a). The scale was used in this study to assess the level of communication related to care for PLH with coworkers or friends among service providers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future strategies should also emphasize training for health professionals to reduce stigma and discrimination and increase empathy, thereby creating a more supportive clinical environment for PLHIV ( 20,29,30 ). Li and colleagues ( 31 ) found that stigma reduction was an unintended consequence of an HIV prevention program conducted among community popular opinion leaders.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of these interactions requires the development and implementation of multi-layered interventions [17,[45][46][47][48] in health care settings that are underpinned by political will, financial support, and the commitment of institutions to stigma reduction [37,49]. These kinds of macro supports for interpersonal and organizational interventions are imperative if interventions are to be successful.…”
Section: Discussionmentioning
confidence: 99%